INDUCTIVE AND DEDUCTIVE METHODS IN TEACHING GRAMMAR FOR ESL LEARNERS - Abdullaeva , Sevara; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
Teaching is an interesting but in another site quite difficult process for every teacher,especially if it is ESL learners.For teaching properly, teacher should be not only skillful but also flexible, they should know each student’s psycology and able to be in each student’s place,to think like them,to learn like them.Knowing all learning styles gives more opportunity to teach a language in an effective way. This article gives information about the difference of four learning styles, how to conduct the lesson using them, their effectiveness for each student and their benefits for teachers. The main aim of this article contains to provide some tips of styles for teachers while teaching ESL learners. Furthermore, it gives some techniques how to combine all the styles (visual, auditory, kinesthetic,readin writing ) into one lesson.